Excitation of Surface Electromagnetic Waves at the Silver/NaCl Aqueous Solution Interface - Kononov, M.A.; Pustovoy, V.I.; Svetikov, V.V.; Usievich, B.A. (Frontiers in Physics, 2021)
This paper presents the results of studying the excitation of a surface electromagnetic wave (SEW) at the interface between silver / aqueous NaCl solution. Comparative analyses of the parameters of SEW excitation in distilled water and in aqueous NaCl solutions with concentrations of 10-3, 10-4, 10-6, and 10-10M were made. The technique used for measuring the dynamics of the excitation parameters of SEW has shown its applicability for studying highly dilute solutions.